Preliminary Study On Yoke Sizing Of Concentric Magnetic Gear - Mohd Ab Halim, Mohd Firdaus; Sulaiman, Erwan; Soomro, Irfan Ali; Syed Othman, Syed Muhammad Naufal (World Academy of Research in Science and Engineering, 2020)
In this paper, torque, torque density, efficiency and efficiency slope of concentric magnetic gear (CMG) at different yoke sizes are evaluated using 2D finite element. Transient analysis when eddy current loss included and excluded are simulated. Efficiency to speed o used in this study is similar to the original gear ratio, 5.5. The change in the yoke size also effect the torque density of the CMG. The finding showed that the change in size at the outer rotor yoke influence the torque and efficiency the most. The smallest outer rotor yoke yields higher torque density of 55% then the average value in this study and slower gear efficiency degradation